Evidence that the modulator of the glucocorticoid-receptor complex is the endogenous molybdate factor. - Bodine, P V (Proc Natl Acad Sci U S A, 1988)
We have recently purified the modulator of the glucocorticoid-receptor complex from rat liver. Purified modulator inhibits glucocorticoid-receptor complex activation and stabilizes the steroid-binding ability of the unoccupied glucocorticoid receptor. Since these activities are shared by exogenous sodium molybdate, modulator appears to be the endogenous factor that sodium molybdate mimics. In this report, we present additional evidence for the mechanism of action of purified modulator. (i) Molybdate and modulator inhibit receptor activation as measured by DNA-cellulose binding, DEAE-cellulose chromatography, and Sepharose 4B gel filtration. (ii) The ability of molybdate and modulator to inhibit receptor activation and stabilize the unoccupied receptor appears to be additive. (iii) Scatchard analysis of heat-destabilized unoccupied receptors indicates that the number of steroid-binding sites is reduced during destabilization, whereas the steroid dissociation constant remains unchanged. Molybdate and modulator stabilize the receptor by maintaining the number of steroid-binding sites. (iv) Molybdate and modulator do not inhibit alkaline phosphatase-induced destabilization of the unoccupied receptor. However, alkaline phosphatase-induced destabilization is reversed by the addition of dithiothreitol in the presence, but not in the absence, of molybdate or modulator. These results suggest that the mechanism of action for modulator is identical to that of sodium molybdate, and we propose that modulator is the endogenous molybdate factor for the glucocorticoid receptor.